Science-Based Thematic Cultural Art Learning in Primary School (2013 Curriculum) - Handayaningrum, Warih (Harmonia: Journal of Arts Research and Education, 2016)
This study is aimed at discussing the development result of thematic cultural art subject’s learning material based on science for primary school (2013 curriculum). This study is expected to inspire teacher to develop learning material that may explore artworks exist in our living environment (based on the context of children’s environment). This study applies steps in developmental research collaboration by Borg & Gall (1989) and Puslitjaknov (2008) to create the product. The development stages comprise observation in several primary schools in Surabaya, Gresik, and Sidoarjo that has implemented 2013 curriculum that is followed up by stages of development. Furthermore, prototype of cultural and art thematic learning material development results are verified by learning material experts, material expert, primary school teacher, and revised afterwards. The result of this research development is a set of teacher and student books. Science-based cultural art here means cultural art learning as the main medium to introduce local culture products (music, drawing, dance, and drama) by integrating mathematics, sciences, Bahasa Indonesia, and local language subjects. Cultural art products in the form of dance, music, drawing, dramas) will help children to understand a simple mathematical concept, such as: two-dimensional figure, geometry, comparing or estimating longer-shorter, smaller-bigger, or more-less.